2020
DOI: 10.1111/1744-9987.13585
|View full text |Cite
|
Sign up to set email alerts
|

Association between pill burden and interdialytic weight gain in patients with hemodialysis: A multi‐center cross‐sectional study

Abstract: High daily pill burden affects quality of life and mortality. High interdialytic weight gain (IDWG) is associated with increased mortality. We examined the association between pill burden and IDWG in hemodialysis patients. This cross‐sectional study was conducted in six dialysis centers in Japan in June 2017. The exposure was the number of daily tablets, and outcome was defined as 1 day of relative IDWG divided by post‐dialysis weight from the previous session. Among 188 outpatients (mean age, 68.7 [SD, 10.3] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…The mean (15.1) and median (14.1) values of the total pill burden in this study are lower than those in previous reports [6,8,[10][11][12]. On the other hand, the pill burden from PBs (mean 6.4 pills) is much less than those found in other two reports [6,11] and only slightly fewer than that (mean 6.7 pills) in Japan in the international Dialysis Outcomes and Practice Patterns Study (DOPPS) [9].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The mean (15.1) and median (14.1) values of the total pill burden in this study are lower than those in previous reports [6,8,[10][11][12]. On the other hand, the pill burden from PBs (mean 6.4 pills) is much less than those found in other two reports [6,11] and only slightly fewer than that (mean 6.7 pills) in Japan in the international Dialysis Outcomes and Practice Patterns Study (DOPPS) [9].…”
Section: Discussioncontrasting
confidence: 79%
“…Polypharmacy causes a variety of problems, including adverse drug interaction events, lower quality of life, inappropriate (incorrect, over-, and under-) prescriptions, poor medication adherence, and increased health care costs [1][2][3]. Although there is currently no clear-cut definition of polypharmacy [2,4], chronic dialysis patients have to take many pills of oral drugs, as such bear high pill burden, to treat multiple comorbidities [5][6][7][8][9][10][11][12]. The symptoms and severity of complications vary greatly among dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that dialysis patients have several dosing opportunities in a day (median 6 [4][5][6][7] times/ day/patient) and that more than 40% of patients took their drugs more than seven times. Although we could not compare the daily dosing frequency of dialysis patients with that of other chronic disease patients in our or other facilities, it is easily considered to be higher.…”
Section: Discussionmentioning
confidence: 61%
“…Polypharmacy is a condition in which patients are prescribed more drugs than necessary, and a high pill burden is a condition in which a large number of drug pills are prescribed. Chronic hemodialysis patients are prone to polypharmacy and high pill burden situations to treat multiple complications [1][2][3][4][5][6], resulting in poor medication adherence [7][8][9]. Under these circumstances, phosphate binders (PBs), which are used by most dialysis patients, account for a large proportion of the daily pill burden compared to other drugs [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation